The impact of culture on the right of women to participate in public affairs : a comparative analysis of Swazi and Buganda Kingdoms - Tamale, Sylvia (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2003.